Synthesis, Characterization And Physicochemical Investigations Of Chitosan Built Hydrogel For Controlled Drug Delivery Applications - Ullah, Faheem (2018)
This study attempted to clarify the influence of induced sensitivity on the structural, physicochemical, drug loading and release profiles of chitosan built hydrogel for controlled drug delivery applications. Different series of hydrogel based on free radical copolymerization of chitosan with poly (ethylene glycol) methyl ether methacrylate, acrylamide-co- methacrylic acid and alginic acid were synthesized and functionalized with induced micellization, glucose sensitivity and hydrophilicity for extended interfaces with drug solutions. The overall hydrogel were characterized by using different techniques as FT-IR, 13C-NMR, SEM, AFM, TGA, DSC, DLS and UV-Visible spectroscopy. The effect of various stimuli (pH, glucose, temperature, ionic strength, urea) on physicochemical properties and the in vitro drug loading versus release profiles of various model drugs from the hydrogel matrices was investigated at physiological conditions. The results suggested that the molecular weight of chitosan does not effect the Critical Micelle Concentration (CMC) and Lower Critical Solution Temperature (LCST). The morphology of hydrogel Analyzed by SEM and AFM analysis revealed hydrogel with high internal surface areas resulted with low diffusional resistance. The model drugs Fluorescein, Rhodamine and Bromocresol green with 75.94%, 65.63% and 76% release profiles were obtained due to electrostatic complexation and extended interfaces of selective ligands with drug solutions. The drug release was observed due to concentration gradient, core to surface and surface to aqueous medium by diffusion and were detected spectroscopically. The diffusion coefficeint (n≈ 0.7) suggested Non- Fickian mechanism of drug release through water diffusion and hydrogel relaxation. In vitro degradation of 20% and 38% was achieved for hydrogel with induced hydrophilicity in simulated gastric and intestinal fluids for 400 h (2 weeks) through bulk erosion. Therefore, this study contributes to the knowledge of chitosan built hydrogel as high performance biomaterials designed for controlled drug delivery applications.